Den helhedsorienterede analyse i beskæftigelsesindsatsen - Christensen, Anders Bøggild (Tidsskrift for Professionsstudier, 2025)
The holistic view is a fundamental concept in the social work profession. It is considered a basic ambition to be able to develop a holistic analysis and carry out a holistic effort. However, it has proven difficult to specify how this should be done, and the established models are rarely of practical help. This article examines how holistic analyses are conducted with activity-ready recipients of social assistance with the aim of developing more practice-oriented understandings of working with the holistic view. The article highlights the importance of exercising professional judgment in holistic analyses.